Soil Amendment with Biosolids and Inorganic Fertilizers: Effects on Biochemical Properties and Oxidative Stress in Basil (Ocimum basilicum L.) - Nadia de la Portilla; Rocio Vaca; Martha E. Mora-Herrera; Liliana Salinas; Pedro del Aguila; Gustavo Yañez-Ocampo; Jorge Lugo (Agronomy, 2020)
We investigated changes in biochemical activity of a soil cultivated with Ocimum basilicum L. plants and in the oxidative stress of plants caused by the addition of biosolids and inorganic fertilizer. A greenhouse experiment was set up; it consisted of pots containing basil plants to which different treatments with biosolids and fertilizers were added. After 10 and 210 days of the incorporation of the treatments, both the biochemical properties and oxidative stress of the plants were evaluated. Mineralization of nitrogen (N) and respiratory activity increased with a higher dose of biosolid after 10 days of application. After 210 days, there were no changes in the mineralization of N and respiratory activity, catalase showed an increase, while microbial biomass carbon decreased. In relation to the oxidative stress, there was a decrease in the anthocyanin antioxidant capacity, and 2,2-diphenyl-1-picrylhydrazyl (DPPH), total flavonoids, and phenolic compounds were observed in soils treated with biosolids. The results indicated that the biochemical properties of the soil were favored in the presence of biosolids because they increased, especially after 10 days of application. The antioxidant capacity decreased in the presence of biosolids, which suggests that the amendment does not affect such capacity, and therefore oxidative stress could be reduced.